Use of chemical fractionation to understand partitioning of biomass ash constituents during co-firing in fluidized bed combustion - Teixeira, P. Alexandra (2014)
Three species of biomass origin (straw pellets, olive cake and wood pellets) and two coals from different countries (Coal Polish and Coal Colombian) have been studied to understand the fate of their ash forming matter during the combustion process and to investigate the influence of co-firing biomass with coal. Three different approaches to investigate the ash behaviour were employed: (1) chemical fractionation analysis to evaluate the association/reactivity of ash forming elements in the fuels as a prediction tool, (2) establishment of elements partitioning in ash streams produced in the combustion and co-combustion trials, and (3) evaluation of enrichment factors of elements in the ash streams. The chemical fractionation analysis was applied to all fuels used to evaluate how the association/reactivity of elements making up ash may influence their behaviour during combustion. Combustion tests were carried out on a pilot scale fluidized bed combustor (FBC). Four ash streams were obtained at different locations. The uncertainty of measurements was estimated allowing a critical evaluation of mass balances over the combustion system and the partitioning of elements in the ash streams. The enrichment factors of elements in the several ash streams were estimated, incorporating uncertainties associated with analytical measurements. Results obtained showed that for FBC the relation between the chemical fractionation and the experimental partitioning is strongly affected by elutriation of particles. The element enrichment factor estimated for each ash stream, using Al as a reference element, revealed better correlations with the elements reactivity obtained by chemical fractionation because it overcomes particles elutriation effects. Nevertheless, it was observed that the reactivity estimated by chemical fractionation could not be solely interpreted as tendency of the elements to volatilize on FBC system, as reaction in bed zone of boiler may also occur retaining reactive elements.